MODELLING A SUSTAINABILITY MODEL OF ISLAMIC MICROFINANCE INSTITUTIONS - Yuli Indah Sari; Widiyanto bin Mislan Cokrohadisumarto (Journal of Islamic Monetary Economics and Finance, 2019)
Islamic microfinance institutions (IMFIs) – such as Baitul Maal wat Tamwil (BMT - with cooperative legal entities), established in Indonesia as part of the shariah-compliant financial industry sector (part of the halal sector) – need to maintain their sustainability in order to encourage poverty alleviation and economic growth. In observing the sustainability of BMT, there has been relatively little research involving aspects of the quality of the human resources that carry out internal activities. Therefore, the aim of this study is to create a model that is useful for predicting the sustainability of IMFIs, especially BMT, based on variables that are considered important, namely financing growth, Islamic human capital, fraud and Islamic leadership. The model was analysed using multiple regression analysis based on the stepwise method. The primary data (cross-sectional) were obtained in 2019 using questionnaires completed by 105 respondents comprising the administrators and managers of BMTs in Semarang and Pekalongan, Central Java, Indonesia. We found that only two variables have a significant influence on the sustainability of IMFIs: financing growth and Islamic human capital. Practitioners can apply the results of the study to improve the performance of Islamic microfinance, especially BMT, through the distribution of funding in the context of economic improvement (especially micro-enterprise), spiritual strengthening for human resources, risk prevention and appropriate leadership criteria.